Mechanisms controlling soil carbon turnover and their potential application for enhancing carbon sequestration - Jastrow, Julie D.; Amonette, James E.; Bailey, Vanessa L. (Climatic change, 2007)
In addition to increasing plant C inputs, strategies for enhancing soil C sequestration include reducing C turnover and increasing its residence time in soils. Two major mechanisms, (bio) chemical alteration and physicochemical protection, stabilize soil organic C (SOC) and thereby control its turnover. With (bio)chemical alteration, SOC is transformed by biotic and abiotic processes to chemical forms that are more resistant to decomposition and, in some cases, more easily retained by sorption to soil solids. With physicochemical protection, biochemical attack of SOC is inhibited by organomineral interactions at molecular to millimeter scales. Stabilization of otherwise decomposable SOC can occur via sorption to mineral and organic soil surfaces, occlusion within aggregates, and deposition in pores or other locations inaccessible to decomposers and extracellular enzymes. Soil structure is a master integrating variable that both controls and indicates the SOC stabilization status of a soil. One potential option for reducing SOC turnover and enhancing sequestration, is to modify the soil physicochemical environment to favor the activities of fungi. Specific practices that could accomplish this include manipulating the quality of plant C inputs, planting perennial species, minimizing tillage and other disturbances, maintaining a near-neutral soil pH and adequate amounts of exchangeable base cations (particularly calcium), ensuring adequate drainage, and minimizing erosion. In some soils, amendment with micro- and mesoporous sorbents that have a high specific surface - such as fly ash or charcoal - can be beneficial. [PUBLICATION ABSTRACT]